Caracterização de uma micro pluma de plasma com descarga de argônio - Vasques, Gustavo Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Plasma micro plumes were generated by an experimental arrangement constituted by a surgical needle, a ring and a dielectric tube by a dielectric barrier discharge (DBD). The emitted light was collected with an optical fiber and sent to a photomultiplier to study the integrated luminosity. It was also used a spectrometer to analyze the spectral lines. Analyzing the integrated light emission was possible to see the light peaks related to the plasma bullets emitted by the needle tip. The integrated light in a half-cycle of the applied voltage was greater at the positive ones. About the argon discharges it was observed lines of ArI and ArII. Over the plasma plume the line of 727.52 nm of ArI was extinguished as long as the line of 337.64 nm of ArII was raising its luminosity. Those measurements gave us the length of 11 ± 1 mm of the plasma plume. The power was acquired by measuring the current at a resistor connected in series with the plasma. The average power changes according with the flux of the gas, the power drops as long as the flux raises. Its maximum and minimum is 0,92 ± 0,02 W and 0,72 ± 0,03 W, respectively. After applying the plasma plume at a high-density polyethylene surface, it was observed an alteration of its surface energy, it has become hydrophilic. The greater change of the contact angle happened with the lowest power, which reduce from 87° ± 11° to 33° ± 5°

Micro plumas de plasma foram geradas através de um arranjo com uma agulha cirúrgica, um anel e um capilar através de uma Descarga por Barreira Dielétrica (DBD). A luz gerada foi coletada por uma lente e enviada por meio de uma fibra óptica a uma fotomultiplicadora para estudo da emissão espectral integrada. Um espectrômetro foi também usado para analisar as linhas espectrais. A análise da luz integrada mostrou uma emissão contínua de luz sobrepostas a um pico relacionada a projéteis de plasma (bullets) emitidas a partir da ponta da agulha. Esta emissão integrada em um semi-ciclo da tensão aplicada mostrou uma intensidade mais elevada em semi-ciclos positivos. Nas descargas com argônio foram observadas linhas do ArI e ArII. Ao longo da pluma de plasma a linha do 727,52 nm do ArI se extinguem à medida que há um aumento progressivo da intensidade da linha 337,64 nm do ArII. Essas medições fornecem um comprimento para a pluma de 11 ± 1 mm. A análise da potência foi efetuada através da corrente em um resistor em série com a descarga. A potência média varia proporcionalmente ao fluxo do gás e diminui para fluxo muito elevado. Tem um valor máximo de 0,92 ± 0,02 W e mínimo de 0,72 ± 0,03 W. Ao aplicar a pluma de plasma em uma superfície de polietileno de alta densidade, houve uma alteração da energia superficial do material, tornando a superfície hidrofílica. A maior alteração do ângulo de contato foi com a menor potência onde reduziu de 87° ± 11° para 33° ± 5°
Characterization of a micro plume of plasma with discharge of argon
Keywords: Plasma (Gases ionizados); Argônio; Descargas luminosas; Plasma (Ionized gases)